2018
DOI: 10.1161/hypertensionaha.117.10360
|View full text |Cite
|
Sign up to set email alerts
|

Selective Mineralocorticoid Receptor Cofactor Modulation as Molecular Basis for Finerenone’s Antifibrotic Activity

Abstract: Mineralocorticoid receptor antagonists (MRAs) reduce morbidity and mortality in chronic heart failure. Novel nonsteroidal MRAs are currently developed and need to be pharmacologically characterized in comparison to classical steroidal MRAs. A mouse model of cardiac fibrosis induced by short-term isoproterenol injection was used to compare the nonsteroidal MRA finerenone and the steroidal MRA eplerenone in equi-efficient systemic MR blocking dosages. Molecular mechanisms were studied in MR-expressing H9C2/MR+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 183 publications
(183 citation statements)
references
References 28 publications
5
147
0
5
Order By: Relevance
“…Comparison of the observational arm with the control group in the clinical trial allows proving the diagnostic and prognostic performance of HF1; comparison of control and intervention groups in the randomized trial allows proving the efficacy and cost‐effectiveness of HF1‐guided early pharmacological intervention. Drugs to be considered include a selective aldosterone receptor antagonist (finerenone), a selective inhibitor of the sinoatrial pacemaker If current (ivabradine), an angiotensin receptor neprilysin inhibitor (sacubitril/valsartan), or an orally active soluble guanylate‐cyclase stimulator (vericiguat) . In the intervention arm, the experimental drug will be administered on top of usual treatment, as done in many contemporary trials, although—should sacubitril/valsartan be the experimental drug—dual inhibition of the renin–angiotensin system as defined in current guidelines must be avoided and the angiotensin receptor neprilisyn inhibitor will replace previous treatment with an angiotensin‐converting enzyme inhibitor or an angiotensin receptor blocker.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Comparison of the observational arm with the control group in the clinical trial allows proving the diagnostic and prognostic performance of HF1; comparison of control and intervention groups in the randomized trial allows proving the efficacy and cost‐effectiveness of HF1‐guided early pharmacological intervention. Drugs to be considered include a selective aldosterone receptor antagonist (finerenone), a selective inhibitor of the sinoatrial pacemaker If current (ivabradine), an angiotensin receptor neprilysin inhibitor (sacubitril/valsartan), or an orally active soluble guanylate‐cyclase stimulator (vericiguat) . In the intervention arm, the experimental drug will be administered on top of usual treatment, as done in many contemporary trials, although—should sacubitril/valsartan be the experimental drug—dual inhibition of the renin–angiotensin system as defined in current guidelines must be avoided and the angiotensin receptor neprilisyn inhibitor will replace previous treatment with an angiotensin‐converting enzyme inhibitor or an angiotensin receptor blocker.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Furthermore, finerenone exhibits a more balanced cardio‐renal organ distribution in comparison with the steroidal MR antagonists because of their differing physicochemical properties . These differences might ultimately lead to a different pharmacology of steroidal MR antagonists and non‐steroidal finerenone; however it is not known whether finerenone opposes metabolic syndrome‐related end‐organ damage. The aim of the present study, therefore, was to determine whether finerenone opposes the development of metabolic syndrome‐related cardiac and renal dysfunction, and to investigate the possible mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…or Tnx (tenascin-X) [42]. Studies using selective MR or GR antagonists confirmed MR-dependent expression of these genes in H9C2 cells [43,44]. In heart tissue from untreated mice overexpressing MR in cardiac myocytes, microarray analysis revealed 24 transcripts upregulated and 22 transcripts downregulated.…”
Section: Impact Of Aldosterone and Mr On Gene Expression In The Cardimentioning
confidence: 93%
“…However, GEMIN4 actions are not restricted to MR, leaving NF-YC as the only described MR-specific corepressor [77]. Just recently, a specific MR cofactor modulation has been proposed as a molecular mechanism for the differential antifibrotic properties of the novel nonsteroidal MR antagonist finerenone when compared to steroidal MR antagonists [78].…”
Section: Co-regulators Of Mr Activitymentioning
confidence: 99%